Hypervirulent group A Streptococcus emergence in an acaspular background is associated with marked remodeling of the bacterial cell surface (2018)
Inactivating mutations in the control of virulence two-component regulatory system (covRS) often account for the hypervirulent phenotype in severe, invasive group A streptococcal (GAS) infections. As CovR represses production of the anti-phagocytic hyaluronic acid capsule, high level capsule production is generally considered critical to the hypervirulent phenotype induced by CovRS inactivation. There have recently been large outbreaks of GAS strains lacking capsule, but there are currently no data on the virulence of covRS-mutated, acapsular strains in vivo. We investigated the impact of CovRS inactivation in acapsular serotype M4 strains using a wild-type (M4-SC-1) and a naturally-occurring CovS-inactivated strain (M4-LC-1) that contains an 11bp covS insertion. M4-LC-1 was significantly more virulent in a mouse bacteremia model but caused smaller lesions in a subcutaneous mouse model. Over 10% of the genome showed significantly different transcript levels in M4-LC-1 vs. M4-SC-1 strain. Notably, the Mga regulon and multiple cell surface protein-encoding genes were strongly upregulated–a finding not observed for CovS-inactivated, encapsulated M1 or M3 GAS strains. Consistent with the transcriptomic data, transmission electron microscopy revealed markedly altered cell surface morphology of M4-LC-1 compared to M4-SC-1. Insertional inactivation of covS in M4-SC-1 recapitulated the transcriptome and cell surface morphology. Analysis of the cell surface following CovS-inactivation revealed that the upregulated proteins were part of the Mga regulon. Inactivation of mga in M4-LC-1 reduced transcript levels of multiple cell surface proteins and reversed the cell surface alterations consistent with the effect of CovS inactivation on cell surface composition being mediated by Mga. CovRS-inactivating mutations were detected in 20% of current invasive serotype M4 strains in the United States. Thus, we discovered that hypervirulent M4 GAS strains with covRS mutations can arise in an acapsular background and that such hypervirulence is associated with profound alteration of the cell surface.